Consequences of Civil Conflict - Gates, Scott; Hegre, Håvard; Mokleiv Nygård, Håvard; Strand, Håvard (World Bank, Washington, DC, 2017)
This paper reviews the literature on the development consequences of internal armed conflict and state fragility and analyzes the relationship using data from World Development Indicators, Ukraine Corporate Development Project UCDP/Peace Research Institute of Oslo (PRIO) Armed Conflict Data (ACD), and World Bank state fragility assessments. Our main focus is on a set of development indicators that capture seven of the Millennium Development Goals, but the author also look briefly into the effect of conflict and fragility on growth, human rights abuses, and democratization. The author analyze these relationships using a variety of methods, averages by conflict and fragility status; cross-sectional regression analyses of change in each indicator over the time frame for which we have data; fixed-effects regression analyses of the impact on each indicator for each five-year period 1965-2009; as well as occasional panel time series models and matching techniques. In section two, the author summarizes the methodological choices and presents our conflict data. Section three summarizes the results of our analysis. Finally, section four analyzes the effects of internal armed conflict on the attainment of the individual Millennium Development Goals (MDGs).